Educating for peace and human rights : an introduction - Hantzopoulos, Maria; Bajaj, Monisha (London, England : Zed Books, 2021)
"Over the past five decades, both peace education and human rights education have emerged distinctly and separately as global fields of scholarship and practice. Promoted through multiple efforts (the United Nations, civil society, grassroots educators), both of these fields consider content, processes, and educational structures that seek to dismantle various forms of violence, as well as move towards cultures of peace, justice and human rights. Educating for Peace and Human Rights Education will introduce students and educators to the challenges and possibilities of implementing peace and human rights education in diverse global sites. The book untangles the core concepts that define both fields, unpacking their histories, conceptual foundations, models, and key research findings to consider their intersections, convergences and divergences. Including an annotated bibliography, the book sets forth a comprehensive research agenda, allowing students the chance to situate a research project in conversation with the global fields of peace and human rights education"--
Introduction -- 1. Peace Education: The Foundations and Future Directions of a Field -- 2. Peace Education in Practice: Examples from the United States -- 3. Human Rights Education: Foundations, Frameworks & Future Directions -- 4. Human Rights Education in Practice: Examples from South Asia -- 5. Bridging the Fields: Conceptualizing Dignity & Transformative Agency in Peace & Human Rights Education -- 6. Concluding Thoughts and the Way Ahead Appendix A: Annotated List of Further Reading in Peace and Human Rights Education Index
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Peace -- Study and teaching; Human rights -- Study and teaching; Moral & social purpose of education; Electronic books